Certain Bipolar Neutrosophic Competition Graphs - Akram, Muhammad (IndoMS, 2018)
Different competitions of the real world have been designed by the bipolar neutrosophiccompetitions graphs. In this paper, we first introduce the concept of p-competition bipo-lar neutrosophic graphs. We then define generalization of bipolar neutrosophic competitiongraphs called m-step bipolar neutrosophic competition graphs. Further, we present somerelated bipolar neutrosophic graphs, including m-step bipolar neutrosophic neighbourhoodgraphs, bipolar neutrosophic economic competition graphs and m-step bipolar neutrosophiceconomic competition graphs. Finally, we describe an application of m-step bipolar neutro-sophic competition graphs.